Effects of stocking density on the nutrient budget and growth of the western king prawn (Penaeus latisulcatus Kishinouye) in a recirculating aquaculture system - Khoi, Le; Fotedar, Ravi (Blackwell, 2010)
Intensification in the commercial culture of prawns can have a significant impact on the water quality and hence on the survival, growth and the surrounding environment. The present study aims to evaluate the effects of stocking density on the water quality and performance of the western king prawns (Penaeus latisulcatus) and the nutrient budget of the culture environment. Four stocking densities of 4, 8, 16 and 32 prawns m−2 were tested in 12 recirculating systems. Prawn weight and specific growth rate increased with decreasing stocking density, while the survival rate showed the reverse trend. The mean total ammonia nitrogen, nitrate nitrogen, total phosphorus and soluble reactive phosphorus were significantly higher (P<0.05) at the higher stocking density. The nutrient budget revealed that the prawns could assimilate only 9.34–20.13% nitrogen and 4.97–11.25% phosphorus of the total nutrient inputs. The drained water at harvest was the major sink of phosphorus and nitrogen at stocking densities of 4, 8 and 16, which accounted for 45.59–64.82% and 44.28–65.62% of the total inputs, respectively, while a significant proportion of nitrogen sunk into the sediment at 32 prawns m−2. The study suggested that the stocking densities of western king prawns can be up to 16 prawns m−2 in the recirculating water environment.